1984
DOI: 10.1159/000242033
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Consumption of Infants with Respiratory Distress Syndrome

Abstract: The objective of this research was to determine the oxygen consumption of newborn infants with respiratory distress syndrome in the first 4 days of life. Serial determinations of oxygen consumption were made in 14 infants with respiratory distress syndrome receiving positive end-expiratory pressures. The mean ( ± SE) oxygen consumption determined at 24, 48, 72, and 96 h postnatal age were 8.3 ± 0.9, 6.5 ± 0.8, 5.5 ± 0.5, and 5.3 ± 0.6 ml/min/kg, respectively. The level of oxygen consumption at 24 h postnatal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The percent change in purine concentrations over time was higher than what we previously observed in clinically stable premature neonates. 3 Because preterm neonates with acute respiratory distress were shown to have oxygen consumption rates that are 60% above normal or recovery levels, 4 the increase in purine concentration over time suggests that sucrose administration may have further altered the ATP utilization to ATP synthesis ratio, resulting in significantly higher products of ATP breakdown. These findings suggest that oral sucrose is not a harmless solution and may have potentially adverse metabolic effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percent change in purine concentrations over time was higher than what we previously observed in clinically stable premature neonates. 3 Because preterm neonates with acute respiratory distress were shown to have oxygen consumption rates that are 60% above normal or recovery levels, 4 the increase in purine concentration over time suggests that sucrose administration may have further altered the ATP utilization to ATP synthesis ratio, resulting in significantly higher products of ATP breakdown. These findings suggest that oral sucrose is not a harmless solution and may have potentially adverse metabolic effects.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, we also reported that oral sucrose, an intervention commonly used to relieve procedural pain, also significantly increased markers of ATP depletion and oxidative stress. 3 These findings were obtained during a clinically required heel lance from subjects who were clinically stable, had a low mean illness severity score (Score for Neonatal Acute Physiology, Perinatal Extension II (SNAPPE-II) score ⩽ 8) 4 and had minimal oxygen requirement. The current report examined the effects of oral sucrose analgesia given before a heel lance in neonates who were intubated and/or had high oxygen requirements (FiO 2 ⩾ 30%).…”
Section: Introductionmentioning
confidence: 99%
“…With chronic in utero hypoxia, consumption is reduced at the expense of growth 13. Compared with levels in resting adults (4 ml/kg/min), neonates have high resting consumption (8.3 (1.8) ml/kg/min26 to 8.3 (0.9) ml/kg/min at 24 hours27). Mature newborn infants increase consumption in the first 24 hours after birth in order to meet the needs of heat generation and respiratory work 13.…”
Section: Oxygen Consumption (Vo 2)mentioning
confidence: 99%